2010
DOI: 10.1016/j.thromres.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammation in regulating platelet production and function: Toll-like receptors in platelets and megakaryocytes

Abstract: Platelets have been extensively studied as hemostatic regulators, stopping uncontrolled flow of blood from an injured vessel and allowing for repair. However, multiple studies have shown that platelets can interact with bacterial proteins, particularly seen during sepsis and inflammation. Immune cells recognize pathogens through Toll-like Receptors (TLRs). These same receptors allow platelets to recognize bacterial proteins and regulate platelet immunity and function. This review examines the TLRs expressed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 49 publications
1
71
0
2
Order By: Relevance
“…8,12,13,[19][20][21] The TLR2 blocking antibody strongly inhibited platelet response to CAP-PEs, whereas nonimmune isotype matched IgG (Figure 2A; supplemental Figure 5A) and TLR3-, TLR4-, and TLR9-specific blocking antibodies had no effect (supplemental Figure 5D-F). TLR2 functions as a heterodimer either with TLR1 or TLR6.…”
Section: Cap-pes Induce Platelet Activationmentioning
confidence: 98%
“…8,12,13,[19][20][21] The TLR2 blocking antibody strongly inhibited platelet response to CAP-PEs, whereas nonimmune isotype matched IgG (Figure 2A; supplemental Figure 5A) and TLR3-, TLR4-, and TLR9-specific blocking antibodies had no effect (supplemental Figure 5D-F). TLR2 functions as a heterodimer either with TLR1 or TLR6.…”
Section: Cap-pes Induce Platelet Activationmentioning
confidence: 98%
“…In addition to collagen, thrombin, and TxA 2 , we assessed responses to stimulation of Toll-like receptors (TLRs) that play important roles in innate immune responses to invading pathogens. 18 Platelets express multiple TLR receptors, 19,20 with the TLR 2/1 complex representing the major functional subtype. [21][22][23][24] These receptors may therefore contribute to the emerging roles of platelets in immune responses and thus also the development of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…7 It has been reported that TPO levels and platelet counts increase after 24 hours of exposure to low-grade endotoxemia 8 ; a possible pathway could be related to TLR2 activation. 7 Previous studies have shown megakaryocyte expression of TLRs, in particular, 1, 2, 4 and 6. 1 The purpose of these receptors and the role of inflammation on megakaryocyte maturation and platelet development is still a matter of debate to which the study by Beaulieu and colleagues significantly contributes.…”
mentioning
confidence: 97%
“…Stimulation of the immune TLR2 on the platelet surface activates phosphoinositide-3-kinase (PI3K) and causes platelet activation and platelet-dependent thrombosis. 7 Inflammatory conditions are known to increase thrombopoietin (TPO) levels, thereby increasing the number of circulating platelets. 7 It has been reported that TPO levels and platelet counts increase after 24 hours of exposure to low-grade endotoxemia 8 ; a possible pathway could be related to TLR2 activation.…”
mentioning
confidence: 99%
See 1 more Smart Citation